CsPbI3 full-inorganic perovskite composite film, preparation method and solar cell
By forming a lead sulfide passivation layer on the surface of the lead acetate doped film of CsPbI3 perovskite solar cells, the problem of poor stability of perovskite solar cells is solved, and higher photoelectric conversion efficiency and stability are achieved.
Patent Information
- Application Number
- CN202411284371.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-11-09
- Filing Date
- 2024-09-13
- Publication Date
- 2025-04-25
AI Technical Summary
The stability of CsPbI3 perovskite solar cells is poor, affecting their photoelectric conversion performance and reliability.
Lead acetate doped with CsPbI3 film, and a lead sulfide passivation layer is formed on its surface in situ. Through the synergistic action of lead acetate and bis(trimethylsilicone)sulfide, a PbS protective layer is formed to improve the stability of the film.
It significantly improves the stability and hydrophobicity of perovskite films, inhibits the degradation of perovskites, enhances the photoelectric conversion efficiency, and provides better long-term stability.
Smart Images

Figure CN119894328A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of solar cells and specifically relates to CsPbI 3 All-inorganic perovskite thin film composite film, preparation method and solar cell. Technical Background
[0002] In the field of all-inorganic perovskite materials, black phase CsPbI 3 It has attracted much attention due to its extremely small band gap (about 1.7eV). According to the Shockley-Queisser limit theory, this property becomes a key prerequisite for realizing high-efficiency solar cells. 3 Perovskite solar cells have poor stability and low long-term stability, which affects the photoelectric conversion performance of the device and restricts the reliability of perovskite solar cells. Summary of the invention
[0003] The technical problem to be solved by the present invention is that CsPbI 3 The poor stability of perovskite solar cells restricts the performance of solar cells. The present invention provides CsPbI 3 The invention discloses an all-inorganic perovskite thin film composite film, a preparation method and a solar cell, which can improve the stability thereof.
[0004] In order to solve the above technical problems, the first solution of the present invention provides: a CsPbI 3 The method for preparing an all-inorganic perovskite composite film comprises the following steps:
[0005] PbI 2 , HI and DMF are mixed to obtain dimethylammonium lead iodide (DMAPbI 3 );
[0006] Stirring CsI and dimethylammonium lead iodide in DMF to obtain a first solution;
[0007] Add Pb(AC) to the first solution 2 , and obtain a second solution;
[0008] The second solution is spin-coated into a film, and Pb(AC) is prepared by annealing at the first temperature. 2 Doped CsPbI 3 film;
[0009] dissolving bis(trimethylsilyl) sulfide (TMS) in chlorobenzene to obtain a third solution;
[0010] Spin-coat the third solution onto Pb(AC) 2 Doped CsPbI 3 The film is annealed at the second temperature to make the Pb(AC) 2Doped CsPbI 3 A lead sulfide passivation layer is formed on the film, wherein the second temperature is lower than the first temperature.
[0011] Among them, Pb(AC) 2 The mass ratio of the dimethylammonium lead iodide to the dimethylammonium lead iodide is (2-9):448.6.
[0012] Wherein, the mass ratio of bis(trimethylsilyl)sulfide to the dimethylammonium lead iodide is (3-8):448.6.
[0013] The concentration of bis(trimethylsilyl) sulfide in the third solution is 3.98-15.75 mg / mL.
[0014] Among them, PbI 2 The mass volume ratio of HI and DMF is (2.2-2.4) g:(1.7-1.9) ml:(4.5-5.5) ml.
[0015] Wherein, the mass ratio of CsI and dimethylammonium lead iodide to DMF is (50-200) mg:(400-450) mg:1 ml.
[0016] Among them, Pb(AC) in the second solution 2 The concentration is 2mg / mL-6mg / mL.
[0017] Among them, the annealing temperature of the annealing treatment at the first temperature is 170-185°C, the annealing time is 10min-15min, the annealing atmosphere is nitrogen, the heating rate is 10°C / min-20°C / min, and the cooling rate is 10°C / min-20°C / min.
[0018] Among them, the annealing temperature of the annealing treatment at the second temperature is 100℃-120℃, the annealing time is 1min-3min, the annealing atmosphere is nitrogen, the heating rate is 5℃ / min-10℃ / min, and the cooling rate is 5℃ / min-10℃ / min.
[0019] The present invention also includes a second technical solution, a CsPbI 3 The all-inorganic perovskite composite film is prepared by the above preparation method, and the all-inorganic perovskite film material includes Pb(AC) 2 Doped CsPbI 3 Thin film layers and set on Pb(AC) 2 Doped CsPbI 3 Lead sulfide passivation layer on the thin film layer.
[0020] The present invention also includes a third technical solution, a solar cell, comprising the above-mentioned all-inorganic perovskite composite film, the all-inorganic perovskite film material comprising Pb(AC) 2 Doped CsPbI 3 Thin film layers and set on Pb(AC) 2 Doped CsPbI 3 Lead sulfide passivation layer on the thin film layer.
[0021] Among them, the all-inorganic perovskite thin film material is used as the light-absorbing layer;
[0022] The solar cell further comprises a hole transport layer, which is arranged on one side of the lead sulfide passivation layer.
[0023] Beneficial effects:
[0024] The preparation method of the present invention adopts lead acetate to dope CsPbI 3 The film was prepared by using bis(trimethylsilyl) sulfide as raw material in lead acetate doped CsPbI 3 The preparation method of the present invention uses lead acetate doping and bis(trimethylsilyl) sulfide as the passivating agent raw materials, and the two interact synergistically. 3 The film allows the acetate ions of lead acetate to react with CsPbI 3 I - Form OHI hydrogen bonds to passivate CsPbI 3 grain boundaries, improving CsPbI 3 The passivation effect of the grain boundary, the lead ions of lead acetate can be freed in CsPbI 3 The lead ions can coordinate with the sulfur bonds in bis(trimethylsilyl) sulfide to form Pb-S bonds, thereby forming an anchored PbS layer on the surface, achieving crystal surface passivation, significantly improving the hydrophobicity of the perovskite film, inhibiting the degradation of the perovskite, and improving the stability of the film. The preparation method of the present invention can be prepared by the combined action of lead acetate doping and bis(trimethylsilyl) sulfide on CsPbI 3 A uniform and dense PbS protective layer is formed in situ on the surface of the film, which can simultaneously realize grain boundary and crystal face passivation, fill vacancies, reduce perovskite surface defects, prevent moisture and oxygen erosion, and improve the hydrophobicity of the perovskite film, thereby providing stability of solar cells and improving photoelectric conversion efficiency. The preparation method of the invention has simple process, no pollution to the environment, low cost, short reaction cycle, and low thermal budget. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The CsPbI 3Process flow chart of an embodiment of a method for preparing an all-inorganic perovskite composite thin film.
[0026] Figure 2a CsPbI prepared in Comparative Example 1 3 Surface scanning electron microscope image of all-inorganic perovskite film;
[0027] Figure 2b CsPbI prepared in Comparative Example 2 3 Surface scanning electron microscope image of all-inorganic perovskite composite film;
[0028] Figure 2c The CsPbI prepared in Example 1 3 Surface scanning electron microscope image of all-inorganic perovskite composite film;
[0029] Figure 3a The CsPbI 3 All-inorganic perovskite thin films and CsPbI 3 XPS Pb 4f photoelectron emission peak spectrum of all-inorganic perovskite composite film.
[0030] Figure 3(b) shows the CsPbI 3 All-inorganic perovskite thin films and CsPbI 3 XPS S1s photoelectron emission peak spectrum of all-inorganic perovskite composite film.
[0031] Figure 4a CsPbI prepared in Comparative Example 1 3 Test diagram of contact angle of all-inorganic perovskite film;
[0032] Figure 4b CsPbI prepared in Comparative Example 2 3 Test diagram of contact angle of all-inorganic perovskite composite film;
[0033] Figure 4c The CsPbI prepared in Example 1 3 Test diagram of contact angle of all-inorganic perovskite composite film;
[0034] Figure 5 It is a test diagram of the photoelectric conversion efficiency stability of the titanium ore solar cell before and after the embodiment and the comparative example;
[0035] Figure 6a The photoluminescence spectrum test of the solar cell light absorbing layer of the embodiment and the comparative example;
[0036] Figure 6b Time-resolved fluorescence spectroscopy test of the solar cell light-absorbing layer of the embodiment and comparative example.
[0037] FIG. 7( a ) is a photoluminescence spectrum test of the solar cell (including the hole transport layer) of the embodiment and the comparative example.
[0038] FIG. 7( b ) is a time-resolved fluorescence spectrum test of the solar cell (including the hole transport layer) of the embodiment and the comparative example.
[0039] Figure 8 It is a photoelectric conversion efficiency diagram of the solar cell before and after devices of the embodiment and the comparative example.
[0040] Fig. 9 1 is a structural diagram of a solar cell according to an embodiment of the present invention. DETAILED DESCRIPTION
[0041] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0042] CxP 3 Perovskite materials have a low tolerance factor, resulting in poor phase stability of their crystal structure. In air, the material is susceptible to corrosion by moisture and oxygen, further weakening its stability. It is worth noting that there are various defects on the surface of perovskite films, including vacancies, interstitials, and antisite defects, which promote the recombination of surface charges and thus reduce device performance.
[0043] In order to solve the above technical problems, the first solution of the present invention provides: a CsPbI 3 The method for preparing an all-inorganic perovskite composite film comprises the following steps:
[0044] PbI 2 , HI and DMF are mixed to obtain dimethylammonium iodide;
[0045] Stirring CsI and dimethylammonium lead iodide in DMF to obtain a first solution;
[0046] Add Pb(AC) to the first solution 2 , and obtain a second solution;
[0047] The second solution is spin-coated into a film, and Pb(AC) is prepared by annealing at the first temperature. 2 Doped CsPbI 3 film;
[0048] dissolving bis(trimethylsilyl) sulfide (TMS) in chlorobenzene to obtain a third solution;
[0049] Spin-coat the third solution onto Pb(AC) 2 Doped CsPbI3 The film is annealed at the second temperature to make the Pb(AC) 2 Doped CsPbI 3 A lead sulfide passivation layer is formed on the film, wherein the second temperature is lower than the first temperature.
[0050] The preparation method of the present invention adopts lead acetate to dope CsPbI 3 The film was prepared by using bis(trimethylsilyl) sulfide as raw material in lead acetate doped CsPbI 3 The preparation method of the present invention uses lead acetate doping and bis(trimethylsilyl) sulfide as the passivating agent raw materials, and the two interact synergistically. 3 The film allows the acetate ions of lead acetate to react with CsPbI 3 I - Form OHI hydrogen bonds to passivate CsPbI 3 grain boundaries, improving CsPbI 3 The passivation effect of the grain boundary, the lead ions of lead acetate can be freed in CsPbI 3 The lead ions can coordinate with the sulfur bonds in bis(trimethylsilyl) sulfide to form Pb-S bonds, thereby forming an anchored PbS layer on the surface, achieving crystal surface passivation, significantly improving the hydrophobicity of the perovskite film, inhibiting the degradation of the perovskite, and improving the stability of the film. The preparation method of the present invention can be prepared by the combined action of lead acetate doping and bis(trimethylsilyl) sulfide on CsPbI 3 The surface of the film is in-situ formed with a uniform and dense PbS protective layer, which can simultaneously realize grain boundary and crystal face passivation, fill vacancies, reduce perovskite surface defects, prevent moisture and oxygen erosion, and improve the hydrophobicity of the perovskite film, thereby providing stability of solar cells and improving photoelectric conversion efficiency. The preparation method of the invention has simple and easy-to-obtain raw materials, no need for expensive instruments and equipment in the preparation process, simple process, no pollution to the environment, low cost, short reaction cycle, and low thermal budget.
[0051] The preparation method of the present invention adopts a simple spin coating device and a thermal annealing device to fill the Pb-S bonds and CsPbI generated by vacancies and defects. 3 Thin film interaction, using the high electron density of S in bis(trimethylsilyl) sulfide (TMS) to interact with Pb on the perovskite surface 2+ After coordination, a low-defect perovskite film was obtained; sulfur reacted with lead on the surface of the perovskite to form a PbS protective layer.
[0052] Among them, Pb(AC) 2 The mass ratio of the dimethylammonium lead iodide to the dimethylammonium lead iodide is (2-9):448.6.
[0053] Wherein, the mass ratio of bis(trimethylsilyl)sulfide to the dimethylammonium lead iodide is (3-5):448.6.
[0054] In the embodiment of the present application, by controlling the content of lead acetate and bis(trimethylsilyl) sulfide, a PbS passivation layer can be prepared well, and the PbS passivation layer is densely formed on the CsPbI 3 On the film, surface vacancies are significantly reduced, defects are reduced, and hydrophobicity is improved to prevent moisture and oxygen erosion.
[0055] The concentration of bis(trimethylsilyl)sulfide in the third solution is 3.98-15.75 mg / mL. By controlling the concentration of bis(trimethylsilyl)sulfide, the concentration of bis(trimethylsilyl)sulfide in CsPbI 3 Improve the film-forming performance on the thin film and improve the density of the formed PbS thin film.
[0056] Among them, PbI 2 The mass volume ratio of HI and DMF is (2.2-2.4) g: (1.7-1.9) ml: (4.5-5.5) ml. By controlling PbI 2 , HI and DMF to increase the yield of dimethylammonium iodination.
[0057] Wherein, the mass ratio of CsI and dimethylammonium lead iodide to DMF is (50-200) mg:(400-450) mg:1 ml.
[0058] Among them, Pb(AC) in the second solution 2 The concentration is 2mg / mL-6mg / mL.
[0059] Among them, the annealing temperature of the annealing treatment at the first temperature is 170-185°C, the annealing time is 10min-15min, the annealing atmosphere is nitrogen, the heating rate is 10°C / min-20°C / min, and the cooling rate is 10°C / min-20°C / min.
[0060] Among them, the annealing temperature of the annealing treatment at the second temperature is 100℃-120℃, the annealing time is 1min-3min, the annealing atmosphere is nitrogen, the heating rate is 5℃ / min-10℃ / min, and the cooling rate is 5℃ / min-10℃ / min.
[0061] The present invention also includes a second technical solution, a CsPbI 3 The all-inorganic perovskite composite film is prepared by the above preparation method, and the all-inorganic perovskite film material includes Pb(AC) 2 Doped CsPbI3 Thin film layers and set on Pb(AC) 2 Doped CsPbI 3 Lead sulfide passivation layer on the thin film layer.
[0062] The present invention also includes a third technical solution, a solar cell, comprising the above-mentioned all-inorganic perovskite composite film, the all-inorganic perovskite film material comprising Pb(AC) 2 Doped CsPbI 3 Thin film layers and set on Pb(AC) 2 Doped CsPbI 3 Lead sulfide passivation layer on the thin film layer.
[0063] Among them, the all-inorganic perovskite thin film material is used as the light-absorbing layer;
[0064] The solar cell further comprises a hole transport layer, which is arranged on one side of the lead sulfide passivation layer.
[0065] Specifically, Fig. 9 As shown, the solar cell from top to bottom includes a silver electrode 1, a molybdenum oxide barrier layer 2, a hole transport layer 3, a PbS passivation layer 4, and a Pb(AC) 2 Doped CsPbI 3 Perovskite film layer 5, tin dioxide electron transport layer 6 and ITO conductive glass 7. The material of the hole transport layer 3 includes Spiro-OMeTAD, and the embodiment of the present application does not limit the material of the hole transport layer 3.
[0066] For ease of understanding, this application provides the following specific embodiments.
[0067] Example 1
[0068] Please refer to Figure 1 As shown, a CsPbI 3 The method for preparing an all-inorganic perovskite composite film comprises the following steps:
[0069] Step 1: PbI 2 , HI and DMF in a mass volume ratio of 2.2 g:1.7 ml:4.5 ml, mixed and stirred at 50 ° C for 12 h, and dried to obtain dimethylammonium lead iodide (DMAPbI 3 )powder.
[0070] Step 2: 180 mg CsI and 448.6 mg DMAPbI 3 The solution was dissolved in 1 ml of DMF at room temperature and stirred to obtain a first solution.
[0071] Step 3: Add 2 mg Pb(AC) to the first solution 2, maintaining its concentration at 2 mg / ml, and stirring at room temperature to obtain a second solution.
[0072] Step 4: Spin-coat the second solution onto ITO glass / SnO 2 The film was formed on the substrate and placed on a heating table at 170°C for annealing to prepare Pb(AC) 2 Doped CsPbI 3 The thin film material has an annealing time of 10 minutes, an annealing atmosphere of nitrogen, a heating rate of 10°C / min, and a cooling rate of 10°C / min.
[0073] Step 5: Dissolve 4 mg of bis(trimethylsilyl) sulfide (TMS) in 1 ml of chlorobenzene to obtain a third solution, wherein the concentration of bis(trimethylsilyl) sulfide is 3.98 mg / mL.
[0074] Step 6: Spin-coat the third solution onto the prepared CsPbI 3 The thin film material is placed on a heating table at a temperature of 100° C. for annealing to form a PbS passivation layer, wherein the annealing time is 3 minutes, the annealing atmosphere is nitrogen, the heating rate is 5° C. / min, and the cooling rate is 5° C. / min.
[0075] The above embodiment does not limit the reaction order. For example, step five can be performed simultaneously with step one, or between step one and step four, or before step one.
[0076] The present invention obtains CsPbI 3 All-inorganic perovskite composite film, all-inorganic perovskite film materials include Pb(AC) 2 Doped CsPbI 3 The thin film layer and the Pb(AC) 2 Doped CsPbI 3 Lead sulfide passivation layer on the thin film layer.
[0077] The present application also includes a solar cell, Pb(AC) 2 Doped CsPbI 3 The thin film layer is used as a light absorbing layer, Pb(AC) 2 Doped CsPbI 3 The electron transport layer SnO is included below the thin film layer. 2 The lead sulfide passivation layer also includes a Spiro-OMeTAD hole transport layer, a MoO 3 The barrier layer and the silver electrode. The embodiments of the present application do not specifically limit the specific materials of the electron transport layer, the hole transport layer and the electrode.
[0078] Embodiment 2:
[0079] A CsPbI 3 The method for preparing an all-inorganic perovskite composite film comprises the following steps:
[0080] Step 1: PbI 2 , HI and DMF in a mass volume ratio of 2.2 g:1.7 ml:4.5 ml, mixed and stirred at 50 ° C for 12 h, and dried to obtain dimethylammonium lead iodide (DMAPbI 3 )powder.
[0081] Step 2: 180 mg CsI and 448.6 mg DMAPbI 3 Dissolve in 1 ml of DMF and stir at room temperature to obtain a first solution;
[0082] Step 3: Add 2 mg Pb(AC) to the first solution 2 , so that its content reaches 2 mg / ml, and continue stirring at room temperature to obtain a second solution;
[0083] Step 4: Spin-coat the second solution on the substrate to prepare a film, and then place it on a heating table at 172°C for annealing for 10 minutes. The annealing atmosphere is nitrogen, the heating rate is 10°C / min, and the cooling rate is 10°C / min to obtain Pb(AC) 2 Doped CsPbI 3 Thin film materials;
[0084] Step 5: Dissolve 5 mg of bis(trimethylsilyl) sulfide (TMS) in 1 ml of chlorobenzene to prepare a third solution, and the obtained solution is 4.975 mg / mL;
[0085] Step 6: Spin-coat the third solution onto the prepared CsPbI 3 The thin film material is placed on a heating table at a temperature of 100° C. for annealing to form a PbS passivation layer, wherein the annealing time is 3 minutes, the annealing atmosphere is nitrogen, the heating rate is 5° C. / min, and the cooling rate is 5° C. / min.
[0086] Embodiment 3:
[0087] A CsPbI 3 The method for preparing an all-inorganic perovskite composite film comprises the following steps:
[0088] Step 1: PbI 2 , HI and DMF in a mass volume ratio of 2.2 g:1.7 ml:4.5 ml, mixed and stirred at 50 ° C for 12 h, and dried to obtain dimethylammonium lead iodide (DMAPbI 3 )powder.
[0089] Step 2: 180 mg CsI and 448.6 mg DMAPbI 3 Dissolve in 1 ml of DMF and stir at room temperature to obtain a first solution;
[0090] Step 3: Add 6 mg of Pb(AC) to the first solution 2 , so that its content reaches 6 mg / mlL, and continue stirring at room temperature to obtain a second solution;
[0091] Step 4: Spin-coat the second solution on the substrate to form a film, and then place it on a heating table at 174°C for annealing for 15 minutes to obtain Pb(AC) 2 Doped CsPbI 3 Thin film materials;
[0092] Step 5: dissolving 8 mg of bis(trimethylsilyl) sulfide (TMS) in 1 ml of chlorobenzene to prepare a third solution, wherein the concentration of bis(trimethylsilyl) sulfide is 7.92 mg / mL;
[0093] Step 6: Spin-coat the third solution onto the prepared CsPbI 3 The thin film material is placed on a heating table at a temperature of 105°C for annealing to form a PbS passivation layer, wherein the annealing time is 3 minutes, the annealing atmosphere is nitrogen, the heating rate is 5°C / min, and the cooling rate is 5°C / min.
[0094] Embodiment 4:
[0095] A CsPbI 3 The method for preparing an all-inorganic perovskite composite film comprises the following steps:
[0096] Step 1: PbI 2 , HI and DMF in a mass volume ratio of 2.2 g:1.7 ml:4.5 ml, mixed and stirred at 50 ° C for 12 h, and dried to obtain dimethylammonium lead iodide (DMAPbI 3 )powder.
[0097] Step 2: 180 mg CsI and 448.6 mg DMAPbI 3 Dissolve in 1 ml DMFF and stir at room temperature to obtain a first solution;
[0098] Step 3: Add Pb(AC) to the first solution 2 , so that its content reaches 9 mg / mL, and continue stirring at room temperature to obtain a second solution;
[0099] Step 4: Spin-coat the second solution on the substrate to form a film, and then place it on a heating table at 178°C for annealing for 9 minutes to obtain Pb(AC) 2Doped CsPbI 3 Thin film materials;
[0100] Step 5: dissolving bis(trimethylsilyl) sulfide (TMS) in chlorobenzene to prepare a third solution;
[0101] Step 6: Spin-coat the third solution onto the prepared CsPbI 3 The thin film material is placed on a heating table at a temperature of 110° C. for annealing to form a PbS passivation layer, wherein the annealing time is 3 minutes, the annealing atmosphere is nitrogen, the heating rate is 5° C. / min, and the cooling rate is 5° C. / min.
[0102] Embodiment 5:
[0103] A CsPbI 3 The method for preparing an all-inorganic perovskite composite film comprises the following steps:
[0104] Step 1: PbI 2 , HI and DMF in a mass volume ratio of 2.2 g:1.7 ml:4.5 ml, mixed and stirred at 50 ° C for 12 h, and dried to obtain dimethylammonium lead iodide (DMAPbI 3 )powder.
[0105] Step 2: 180 mg CsI and 448.6 mg DMAPbI 3 Dissolve in 1 ml of DMF and stir at room temperature to obtain a first solution.
[0106] Step 3: Add Pb(AC) to the first solution 2 , so that its content reaches 10 mg / mL, and continue stirring at room temperature to obtain a second solution.
[0107] Step 4: Spin-coat the second solution on the substrate to form a film, and then place it on a heating table at 180°C for annealing to obtain Pb(AC) 2 Doped CsPbI 3 Thin film materials.
[0108] Step 5: Dissolve 6 mg of bis(trimethylsilyl) sulfide (TMS) in 1 ml of chlorobenzene to prepare a third solution.
[0109] Step 6: Spin-coat the third solution onto the prepared CsPbI 3 The thin film material is placed on a heating table at a temperature of 120° C. for annealing to form a PbS passivation layer, wherein the annealing time is 3 minutes, the annealing atmosphere is nitrogen, the heating rate is 5° C. / min, and the cooling rate is 5° C. / min.
[0110] Example 6
[0111] A CsPbI 3 The method for preparing an all-inorganic perovskite composite film comprises the following steps:
[0112] Step 1: PbI 2 , HI and DMF in a mass volume ratio of 2.4 g:1.9 ml:5.5 ml, mixed and stirred at 60 ° C for 12 h, and dried to obtain dimethylammonium lead iodide (DMAPbI 3 )powder.
[0113] Step 2: Mix 50 mg CsI and 400 mg DMAPbI 3 Dissolve in 1 ml of DMF and stir at room temperature to obtain a first solution.
[0114] Step 3: Add 2 mg Pb(AC) to the first solution 2 , so that its content reaches 2 mg / mL, and continue stirring at room temperature to obtain a second solution.
[0115] Step 4: Spin-coat the second solution on the substrate to prepare a film, and then place it on a heating table at 170°C for annealing for 10 minutes. The annealing atmosphere is nitrogen, the heating rate is 10°C / min, and the cooling rate is 10°C / min to obtain Pb(AC) 2 Doped CsPbI 3 Thin film materials.
[0116] Step 5: Dissolve 4 mg of bis(trimethylsilyl) sulfide (TMS) in 1 ml of chlorobenzene to prepare a third solution.
[0117] Step 6: Spin-coat the third solution onto the prepared CsPbI 3 The thin film material is placed on a heating table at a temperature of 100°C for annealing to form a PbS passivation layer, wherein the annealing time is 1 minute, the annealing atmosphere is nitrogen, the heating rate is 10°C / min, and the cooling rate is 10°C / min.
[0118] Example 7
[0119] A CsPbI 3 The method for preparing an all-inorganic perovskite composite film comprises the following steps:
[0120] Step 1: PbI 2 , HI and DMF in a mass volume ratio of 2.4 g:1.9 ml:5.5 ml, mixed and stirred at 55 ° C for 24 h, and dried to obtain dimethylammonium lead iodide (DMAPbI 3 )powder.
[0121] Step 2: Mix 200 mg CsI and 450 mg DMAPbI3 Dissolve in 1 ml of DMF and stir at room temperature to obtain a first solution.
[0122] Step 3: Add 6 ml of Pb(AC) to the first solution 2 , so that its content reaches 6 mg / mL, and stirring is continued at room temperature to obtain a second solution.
[0123] Step 4: Spin-coat the second solution on the substrate to prepare a film, and then place it on a heating table at 185°C for annealing for 15 minutes. The annealing atmosphere is nitrogen, the heating rate is 5°C / min-5°C / min, and the cooling rate is 5°C / min-5°C / min to obtain Pb(AC) 2 Doped CsPbI 3 Thin film materials.
[0124] Step 5: Dissolve 16 mg of bis(trimethylsilyl) sulfide (TMS) in 1 ml of chlorobenzene to prepare a third solution. The concentration of the third solution is 15.75 mg / mL.
[0125] Step 6: Spin-coat the third solution onto the prepared CsPbI 3 The thin film material is placed on a heating table at a temperature of 120° C. for annealing to form a PbS passivation layer, wherein the annealing time is 3 minutes, the annealing atmosphere is nitrogen, the heating rate is 5° C. / min, and the cooling rate is 5° C. / min.
[0126] Comparative Example 1
[0127] CxP 3 Preparation of all-inorganic perovskite films, including:
[0128] Step 1: PbI 2 , HI and DMF in a mass volume ratio of , were mixed and stirred at 50°C overnight, and dimethylammonium lead iodide powder was obtained after drying.
[0129] Step 2: 180 mg CsI and 448.6 mg DMAPbI 3 The solution was dissolved in 1 ml of DMF at room temperature and stirred to obtain a first solution.
[0130] Step 3: Spin-coat the first solution onto ITO glass / SnO 2 The film was formed on the substrate and placed on a heating table at 170°C for annealing to prepare CsPbI 3 The thin film material has an annealing time of 10 minutes, an annealing atmosphere of nitrogen, a heating rate of 10°C / min, and a cooling rate of 10°C / min.
[0131] Comparative Example 2
[0132] CxP 3 The method for preparing the all-inorganic perovskite composite film comprises the following steps:
[0133] Step 1: PbI 2 , HI and DMF in a mass volume ratio of 2.2 g:1.7 ml:4.5 ml, mixed and stirred at 50°C for 12 h, and then dried to obtain dimethylammonium lead iodide powder.
[0134] Step 2: 180 mg CsI and 448.6 mg DMAPbI 3 The solution was dissolved in 1 ml of DMF at room temperature and stirred to obtain a first solution.
[0135] Step 3: Spin-coat the first solution onto ITO glass / SnO 2 The film was formed on the substrate and placed on a heating table at 170°C for annealing to prepare CsPbI 3 The thin film material has an annealing time of 10 min, an annealing atmosphere of nitrogen, a heating rate of 10 °C / min, and a cooling rate of 10 °C / min.
[0136] Step 4: Dissolve 4 mg of bis(trimethylsilyl) sulfide (TMS) in 1 ml of chlorobenzene to obtain a third solution, wherein the concentration of bis(trimethylsilyl) sulfide is 3.98 mg / mL.
[0137] Step 5: Spin-coat the third solution onto the prepared CsPbI 3 The thin film material is placed on a heating table at a temperature of 100° C. for annealing to form a PbS passivation layer, wherein the annealing time is 3 minutes, the annealing atmosphere is nitrogen, the heating rate is 5° C. / min, and the cooling rate is 5° C. / min.
[0138] The CsPbI prepared in Example 1, Comparative Example 1 and Comparative Example 2 3 All inorganic perovskite films are made into solar cells, and their CsPbI 3 The structure, morphology and performance of all-inorganic perovskite films were tested.
[0139] like Figure 2a is a scanning electron microscope image of the perovskite film of Comparative Example 1, which shows that the surface of the perovskite film exhibits poor morphology and crystal quality, and has holes and obvious grain boundaries; Figure 2b CsPbI of Comparative Example 2 3 Scanning electron microscope image of the all-inorganic perovskite composite film, which shows that the perovskite film only undergoes surface TMS passivation without lead acetate doping to obtain CsPbI 3The all-inorganic perovskite composite film has little change compared to the control sample, with a small amount of granular structures scattered on the surface. This is because the use of TMS alone for passivation does not affect the crystallization process of the perovskite film. TMS only reacts with the Pb on the surface of the perovskite. 2+ Defects form a small number of PbS particles. Figure 2c CsPbI of Example 1 3 Scanning electron micrograph of all-inorganic perovskite composite film with added Pb(AC) 2 The surface morphology of the perovskite film shows that Pb(AC) 2 The crystallization process of perovskite was improved, and the grain size was significantly increased and more dense and uniform. 2 -The surface morphology of the perovskite film treated with TMS changes significantly. This is because TMS reacts with lead to form a protective layer. After the surface is sulfided to form PbS, the PbS passivation layer covers the perovskite film, which significantly reduces the grain boundaries of the perovskite. 2 The combined effect of CsPbI 3 The grain crystallization quality of the perovskite film has been improved and defects have been reduced. At the same time, the PbS passivation layer can prevent erosion by external moisture and oxygen, thereby improving the stability of the perovskite layer.
[0140] like Figure 3a and Figure 3b As shown in Figure 2, X-ray photoelectron spectroscopy (XPS) was used to investigate the effect of surface sulfidation on CsPbI 3 The influence of element binding energy on the surface of perovskite film, such as Figure 7a The S orbital XPS fine spectrum is shown. On the surface of the perovskite film of Comparative Example 2 and Example 1, the S-related characteristic peak at 159.3 eV can be observed, which indicates that after TMS treatment, the perovskite surface contains sulfur. The S-related peak of Example 1 is significantly higher than that of Comparative Example 2, indicating that after TMS treatment of the perovskite with lead acetate added, a PbS passivation layer is formed, and the content of sulfur on the surface increases. Figure 7b It shows Pb 4f XPS fine spectra of orbitals in CsPbI 3 In the perovskite film, we can observe Pb at 138.31eV and 143.02eV. 4f There are two characteristic peaks of Pb(AC) 2 The addition of Pb increases the crystallinity of perovskite and reduces internal defects, resulting in 4f The peak moves toward the direction of lower binding energy. In the perovskite films of Comparative Example 2 and Example 1, Pb 4fThe peak shifts to the direction of higher binding energy, which is due to the strong bond between Pb and sulfur (S). TMS and passivation form a Pb-S high binding energy bond on the surface of the perovskite film, which effectively inhibits the Pb 2+ Defects. The reduction of defects reduces the interface non-radiative recombination effect, thereby promoting the migration of carriers. 4f The binding energy is higher than that of TMS because the Pb-S bond of Example 1 has a higher binding energy. These results indicate that Pb(AC) 2 This effect can only be achieved by the combined action of TMS and cannot be achieved by a single additive alone.
[0141] like Figure 4a-4c As shown in the figure, the results of water contact angle tests on different samples of perovskite films are shown. After TMS passivation, the water contact angle of Comparative Example 2 increased from 57.6° to 68.1° compared with Comparative Example 1. This improvement is due to the TMS passivation treatment that reduces the Pb on the perovskite surface. 2+ The ions form Pb-S bonds with the S bonds in TMS, thereby forming an anchored PbS layer on the surface, which significantly improves the hydrophobicity of the perovskite film. The increased water contact angle can effectively slow down the entry of moisture in the air into the perovskite film, thereby effectively inhibiting the degradation of the perovskite and improving the stability of the film. For the perovskite film of Example 1, the water contact angle increased significantly to 79.3°. This is because the passivation effect of TMS forms a sulfide protective layer on the perovskite surface, which effectively prevents water penetration. These water contact angle test results further prove that Pb(AC) 2 The synergistic effect of lead acetate and TMS formed a uniform sulfide protective layer, which was significantly more hydrophobic than the perovskite film passivated with TMS alone. The above experimental results emphasize that this excellent effect can only be achieved when lead acetate and TMS work together.
[0142] like Figure 5 The long-term stability of different perovskite sample devices was tested, as shown in Figure 5 Compared with Comparative Example 1, the device of Example 1 exhibits better environmental stability, maintaining 90.09% of the original photoelectric conversion efficiency after 500 hours in 25% humidity air. The excellent long-term stability shows that in CsPbI 3 The sulfide protective layer generated on the surface of perovskite effectively prevents the intrusion of moisture from the environment and inhibits the phase decomposition of perovskite.
[0143] like Figure 6a and Figure 6bAs shown, the effect of surface sulfurization on the defects of perovskite films and their carrier complexes was further studied by steady-state fluorescence and transient fluorescence (PL and TRPL). It is worth noting that the PL peak of the perovskite film of Example 1 is significantly higher than that of other samples because Pb(AC) 2 Doping treatment improves the film quality, reduces the defects of perovskite in the body, and TMS passivates the surface defects of perovskite, thereby reducing the non-radiative recombination of carriers. At the same time, the main position of the luminescence peak is around 726nm, indicating that the surface sulfide does not affect CsPbI 3 The perovskite bandgap width. TRPL spectroscopy was used to further study the carrier recombination effect in the perovskite film, such as Figure 6a and 6b As shown. Through the extended exponential fitting lifetime curve, it can be observed that the carrier lifetime of Example 1 is significantly increased. This shows that the body and surface defects of Example 1 are significantly reduced, and the non-radiative recombination of carriers is effectively suppressed.
[0144] like Figure 7a and 7b As shown, in order to further explore the effect of surface sulfurization on carrier transport between the perovskite layer and the hole transport layer, devices prepared from different sample perovskite films were made, and steady-state fluorescence spectroscopy (PL) and transient fluorescence spectroscopy (TRPL) tests were performed from the back of the glass. Figure 7a In the experiment, the PL peak of the sample in Example 1 showed a significant enhancement, indicating that the surface sulfide enhanced the extraction of carriers between the perovskite layer and the hole transport layer. Further research was conducted on the hole transport between the perovskite layer and the hole transport layer. Figure 7b As shown, it was observed that Pb(AC) 2 -TMS surface sulfidation of perovskite films significantly reduces the carrier lifetime of perovskite hole transport. This indicates that the application of surface sulfide slows down the accumulation of interfacial charges and improves the hole extraction efficiency between perovskite and hole transport layer, thereby improving the performance of perovskite solar cell devices.
[0145] like Figure 8 As shown, the photoelectric conversion efficiency of devices prepared from different samples of perovskite films was tested. Compared with the control sample, the open circuit voltage, short circuit current density and fill factor of the perovskite solar cell device of Example 1 were significantly improved, and the photoelectric conversion efficiency of the device reached 16.75%, which was significantly improved compared with the control sample.
[0146] The embodiment of the present invention uses a spin coating device and a thermal annealing device to prepare CsPbI 3The passivation layer formed by the thin film. In the all-inorganic perovskite, the Pb-S bond formed simply by filling the vacancies and defects of the crystal has a limited hydrophobic effect. Therefore, we added an excess of lead-containing compound Pb(AC) to the perovskite solution. 2 Subsequently, bis(trimethylsilyl) sulfide (TMS) was coated on the surface of the film for passivation treatment, in which the S atoms with high electron density coordinated with the Pb+ ions on the surface of the perovskite, thereby obtaining a perovskite film with low defect states. In addition, sulfur reacted with lead on the surface of the perovskite to form a PbS protective layer.
[0147] The inorganic CsPbI doped with lead acetate prepared in the embodiment of the present invention and treated with TMS sulfurization 3 A simple method was used to simultaneously reduce the CsPbI 3 This has the effect of reducing film surface defects and improving hydrophobicity. This provides a basis for the preparation of efficient and stable CsPbI 3 Perovskite solar cells offer a simple and effective approach.
[0148] The bis(trimethylsilyl) sulfide (TMS) prepared in the embodiment of the present invention is surface-sulfurized and doped with Pb(AC) 2 Inorganic CsPbI 3 The perovskite thin film passivation layer has a high passivation effect.
[0149] Combining Example 1 of the present invention and Comparative Examples 1-2, we can observe that the surface of bis(trimethylsilyl) sulfide (TMS) prepared in the present invention is sulfurized and doped with Pb(AC) 2 Inorganic CsPbI 3 The perovskite film passivation layer has an excellent passivation effect. Figure 2c and Figure 2b It can be clearly observed from the comparison that although both Example 1 and Comparative Example 2 of the present invention prepared crystalline CsPbI 3 However, in the embodiment of the present invention, the Pb(AC)-doped film is treated with bis(trimethylsilyl) sulfide (TMS) surface sulfurization. 2 CsPbI 3 Compared with Comparative Example 2, the film exhibits better crystallinity, fewer defects, and stronger hydrophobicity.
[0150] The present invention successfully prepared bis(trimethylsilyl) sulfide (TMS) surface sulfurized and doped with Pb(AC) 2 Inorganic CsPbI 3 The perovskite thin film passivation layer significantly exhibits excellent passivation effect.
[0151] It is obvious that the above embodiments are only for the purpose of clearly describing examples, and do not limit the implementation methods. For those of ordinary skill in the art, various modifications, equivalent substitutions and improvements can be made to the methods and principles of the present invention on the basis of the above description, and these changes should all be included in the protection scope of the present invention. Therefore, it is not necessary to list all possible implementation methods in detail, and the obvious changes or modifications derived therefrom also fall within the protection scope created by the present invention.
Claims
1. A method for preparing a CsPbI3 all-inorganic perovskite composite film, characterized in that: The steps include: PbI2, HI and DMF are mixed and reacted to obtain dimethylammonium lead iodide; Stirring CsI and dimethylammonium lead iodide in DMF to obtain a first solution; Adding Pb(AC)2 to the first solution to obtain a second solution; Spin coating the second solution into a film, and annealing at a first temperature to obtain a Pb(AC)2-doped CsPbI3 thin film; Dissolving bis(trimethylsilyl) sulfide in chlorobenzene to obtain a third solution; The third solution is spin-coated on the Pb(AC)2-doped CsPbI3 film, and annealed at a second temperature to form a lead sulfide passivation layer on the Pb(AC)2-doped CsPbI3 film, wherein the second temperature is lower than the first temperature.
2. A method for preparing a CsPbI3 all-inorganic perovskite composite thin film as described in claim 1, wherein the mass ratio of Pb(AC)2 to dimethylammonium lead iodide is (2-9):448.6; and / or the mass ratio of bis(trimethylsilyl) sulfide to dimethylammonium lead iodide is (3-8):448.
6.
3. A method for preparing a CsPbI3 all-inorganic perovskite composite film as claimed in claim 1, characterized in that: The concentration of bis(trimethylsilyl)sulfide in the third solution is 3.98-15.75 mg / mL.
4. A method for surface sulfurization of a CsPbI3 all-inorganic perovskite film as claimed in claim 1, characterized in that: The mass volume ratio of the PbI2, HI and DMF is (2.2-2.4) g: (1.7-1.9) ml: (4.5-5.5) ml.
5. A method for preparing a CsPbI3 all-inorganic perovskite composite film as claimed in claim 1, characterized in that: The mass ratio of CsI and dimethylammonium lead iodide to DMF is (50-200) mg: (400-450) mg: 1 ml.
6. A method for preparing a CsPbI3 all-inorganic perovskite composite film as claimed in claim 1, characterized in that: The concentration of Pb(AC)2 in the second solution is 2 mg / mL-6 mg / mL.
7. A method for preparing a CsPbI3 all-inorganic perovskite composite film as claimed in claim 1, characterized in that: The annealing temperature of the annealing treatment at the first temperature is 170-185°C, the annealing time is 10min-15min, the annealing atmosphere is nitrogen, the heating rate is 10°C / min-20°C / min, and the cooling rate is 10°C / min-20°C / min.
8. A method for preparing a CsPbI3 all-inorganic perovskite composite film as claimed in claim 1, characterized in that: The annealing temperature of the annealing treatment at the second temperature is 100°C-120°C, the annealing time is 1min-3min, the annealing atmosphere is nitrogen, the heating rate is 5°C / min-10°C / min, and the cooling rate is 5°C / min-10°C / min.
9. A CsPbI3 all-inorganic perovskite composite film, characterized in that: The all-inorganic perovskite thin film material is prepared by the method described in any one of claims 1 to 8, comprising a Pb(AC)2-doped CsPbI3 thin film layer and a lead sulfide passivation layer disposed on the Pb(AC)2-doped CsPbI3 thin film layer.
10. A solar cell, characterized in that: The all-inorganic perovskite composite film according to claim 9, wherein the all-inorganic perovskite film material comprises a Pb(AC)2-doped CsPbI3 film layer and a lead sulfide passivation layer disposed on the Pb(AC)2-doped CsPbI3 film layer; Optionally, the all-inorganic perovskite thin film material is used as a light absorbing layer; Optionally, the solar cell further includes a hole transport layer, and the hole transport layer is arranged on one side of the lead sulfide passivation layer.